The Effect of Cash Management and Working Capital Management on Operational Efficiency: Evidence from Roy Shop Photocopy in Bumi Agung Village - Arent Pramana Putri; Elvera Elvera; Nurlela Nurlela (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Praise and gratitude are expressed to Almighty God for His blessings and grace, enabling the author to complete the thesis entitled “The Effect of Cash Management and Working Capital on Operational Smoothness at Fotocopy Roy Shop in Bumi Agung Village, Dempo Utara District, Pagar Alam City.” This study aims to determine the effect of cash management and working capital on operational smoothness at Fotocopy Roy Shop. This research uses a quantitative method with monthly financial report data from the period of 2023–2025, consisting of 36 data points. The analysis technique used is multiple linear regression with the assistance of the SPSS program. The results of the study indicate that cash management and working capital have a positive and significant effect on operational smoothness. This is evidenced by the results of the t-test and F-test, which show a significance value of 0.000 < 0.05. The coefficient of determination shows an R Square value of 0.571, meaning that cash management and working capital are able to explain the effect on operational smoothness by 57.1%, while the remaining percentage is influenced by other variables outside the scope of this study. Based on the research results, it can be concluded that cash management and working capital have a positive and significant effect on operational smoothness at Fotocopy Roy Shop in Bumi Agung Village, Dempo Utara District, Pagar Alam City.